Liberating Urban Development and the South African Church: A Critical Reflection in Conversation with David Korten and Gustavo Gutierrez - De Beer, Stephan (Concilium, 2019)
In this article I reflect on (post)apartheid cities, from the perspective of spatial (re)segregation, homelessness and precarious housing. I submit that the Church will find herself increasingly isolated from the growing discontent of the urban marginalized, unless it embraces all four generations of development, as outlined by David Korten, whilst rooting herself in a deep commitment to integral liberation, as defined by Gustavo Gutierrez. I conclude by discerning and suggesting seven urgent imperatives for theological action.